Profile of gynecological cytopathology exams carried out in a north Piauí clinic: documental analysis (Research, Society and Development, 2020)
Objective: to analyze the profile of gynecological cytopathology exams found in a municipality in northern Piauí. Methodology: this is a descriptive research with a quantitative and documentary approach in which data from secondary records of a gynecological cytopathology laboratory in northern Piauí, from July to October 2019, were used. Results: there was a greater expression of changes in the age group of 51 years or more on the number of women assisted in the studied period, in addition to the prevalence of coconuts and lactobacilli. Cytopathological examination is one of the priorities of the Ministry of Health, being important in the detection of lesions that can cause cervical cancer. Conclusion: actions to publicize and encourage the performance of this exam can reduce the number of cervical cancer cases in Brazil.